Analysis of the Management and Control System of Trade Receivables on the Effectiveness of the Corporate Cash Flow on PT. Enseval Putera Megatrading, tbk - Syarifah Nuriah; Abdul Rakhman Laba; Muhammad Sobarsyah (Hasanuddin Journal of Business Strategy, 2020)
This study aims to determine the management and control system of trade receivables on the effectiveness of the cash flow company’s at PT. Enseval Putera Megatrading, Tbk. The data source used in this study is the primary data source, obtained directly from the company. The analytical method used for testing the management and control system of receivables on the effectiveness of cash flow is the analysis of financial ratios. In this study, the data used for analysis are qualitative data analysis and financial ratio analysis, namely the activity ratio (RTO, ACP, Arrears Ratio, and Billing Ratio). The results showed that (1) RTO of PT. Enseval Putera Megatrading, the highest rate in 2017 was 189 times, while the lowest RTO was in 2015 which was 115 times. This shows the normal level of turnover. The faster the payment terms, the better for the company, because the faster the working capital embedded in receivables returns to capital or cash, which means the higher the receivables turnover. (2) ACP or the average age of collection of receivables applied by companies, especially the value in 2017 is 2 days. This means that the company has been effective in managing its accounts receivable because the standard for collecting receivables set by the company is the repayment limit or due date no later than 7 (seven) to 90 (Ninety) calendar days from the billing statement received by the service user. (3) The Arrears Ratio, namely from 2014-2018, the largest was only 1.11%. This shows that the lower the arrears ratio, the better for the company, which means the company is able to handle its receivables properly. (4) Billing Ratio shows that from 2014-2018 the lowest that is 98.88% shows the greater the value of collectible receivables means the greater the percentage value of the collection ratio so that the better for the company because of the greater return on corporate capital. Then it can be concluded that the Billing Ratio of PT. Enseval Putera Megatrading, it's not working effectively.